Evaluation of BrachyDose Monte Carlo code for HDR brachytherapy: dose comparison against Acuros (R) BV and TG-43 algorithms - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2020)
Aim: The aim of this study is to investigate the accuracy of dose distributions calculated by the BrachyDose Monte Carlo (MC) code in heterogeneous media for high-dose-rate (HDR) brachytherapy and to evaluate its usability in the clinical brachytherapy treatment planning systems. Materials and methods: For dose comparisons, three different dose calculation algorithms were used in this study. Namely, BrachyDose MC code, Eclipse TG-43 dose calculation tool and Acuros (R) BV model-based dose calculation algorithm (MBDCA). Dose distributions were obtained using any of the above codes in various scenarios including 'homogenous water medium scenario', an 'extreme case heterogeneous media scenario' and clinically important 'a patient with a cervical cancer scenario'. In the 'extreme case, heterogeneous media scenario', geometry is a rare combination of unusual high-density and low-density materials and it is chosen to provide a test environment for the propagation of photons in the interface of two materials with different absorption and scattering properties. GammaMed Ir-192 Model 12i Source is used as the HDR brachytherapy source in this study. Dose calculations were performed for the cases where there is either a single source or five sources planted into the phantom geometry in all homogenous water phantom and extreme case heterogeneous media scenarios. For the scenario a patient with a cervical cancer, dose calculations were performed in a voxelized rectilinear phantom, which is constructed from a series of computed tomography (CT) slices of a patient, which are obtained from a CT device. Results: In homogeneous water phantom scenario, we observed no statistically significant dose differences among the dose distributions calculated by any of the three algorithms at almost every point in the geometry. In the extreme case heterogeneous media scenario, the dose calculation engines Acuros (R) BV and BrachyDose are agreed well within statistics in every region of the geometry and even in the points close to the interfaces of low-density and high-density materials. On the other hand, the dose values calculated by these two codes are significantly different from those calculated by the TG-43 algorithm. In the 'a patient with a cervical cancer scenario', the calculated D-2cc dose difference between Acuros (R) BV and BrachyDose codes is within 2% in the rectum and 11% for the bladder and sigmoid. There was no meaningful difference in the mean dose values between MBDCAs in the bone structures. Conclusions: In this study, the accurate dose calculation capabilities of the BrachyDose program in HDR brachytherapy were investigated on various scenarios and, as a MC dose calculation tool, its effectiveness in HDR brachytherapy was demonstrated by comparative dose analysis.
Keywords: AcurosBV; algorithms; BrachyDose; brachytherapy; Monte Carlo; AAPM; DOSIMETRY; RECOMMENDATIONS; UPDATE; IR-192